2006
DOI: 10.1364/ao.45.002911
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing form factor and light collection of multiplex imaging systems by using a cubic phase mask

Abstract: The bulky form factor of traditional optical sensors limits their utility for certain applications. Flat multiplex imaging-sensor architectures face the light-gathering challenges inherent with small collection apertures. We examine a wavefront-coding approach wherein a cubic phase mask is used to increase the aperture sizes of multiplex imaging systems while maintaining the distance from the lens to the detector array. The proposed approach exploits the ability of cubic-phase-mask systems to operate over a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…This extension was realized through the inclusion of a cubic phase mask at the pupil plane to achieve an MTF that was largely invariant to defocus. It was subsequently shown that the exact OTF of this wavefront coding imager for a given phase mask strength α and defocus parameter ψ is given by [7] Hu; ψ…”
Section: Wavefront Coding Imaging System Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This extension was realized through the inclusion of a cubic phase mask at the pupil plane to achieve an MTF that was largely invariant to defocus. It was subsequently shown that the exact OTF of this wavefront coding imager for a given phase mask strength α and defocus parameter ψ is given by [7] Hu; ψ…”
Section: Wavefront Coding Imaging System Characterizationmentioning
confidence: 99%
“…where C and S represent the Fresnel cosine integral and Fresnel sine integral, respectively, whose operands au and bu have been described in [7]. The parameters α and ψ may be expressed in multiples of wavelength.…”
Section: Wavefront Coding Imaging System Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) can be expressed in terms of a Fresnel integrals, as was first recognized in radar engineering [17], and later on in optics [18]- [19]. In Fig.…”
Section: Ambiguity Function and Mtfmentioning
confidence: 99%
“…Cubic phase mask has been demonstrated to generate finite energy Airy beam by modulating a Gaussian beam [1], to extend the depth of imaging field [2] and to increase the aperture sizes of multiplex imaging systems [3]. Based on the concept of cubic phase mask, we present multiple-powered phase masks to convert a plane wave beam into different shaped beams by using different power exponents.…”
Section: Introductionmentioning
confidence: 99%